1999
DOI: 10.1592/phco.19.3.245.30930
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Azithromycin‐Induced Ototoxicity

Abstract: Intravenous azithromycin is increasingly administered for treatment of hospitalized patients with community-acquired pneumonia. Macrolide antibiotics cause ototoxicity, which occurs most frequently when high serum concentrations are achieved. Current dosing guidelines for intravenous azithromycin can result in much higher serum concentrations than is seen with oral administration. We describe a 47-year-old woman who developed complete deafness after receiving 8 days of intravenous azithromycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…For oral azithromycin, the fastest recovery occurred in 5 days and the longest reported timeframe exceeded 3 months, with one unreported follow‐up time . Intravenous azithromycin was associated with recovery 20 days after cessation . For oral erythromycin, dramatic improvements were subjectively reported immediately after cessation and confirmed in other cases at 48 hours .…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…For oral azithromycin, the fastest recovery occurred in 5 days and the longest reported timeframe exceeded 3 months, with one unreported follow‐up time . Intravenous azithromycin was associated with recovery 20 days after cessation . For oral erythromycin, dramatic improvements were subjectively reported immediately after cessation and confirmed in other cases at 48 hours .…”
Section: Resultsmentioning
confidence: 73%
“…26,29 Intravenous azithromycin was associated with recovery 20 days after cessation. 62 For oral erythromycin, dramatic improvements were subjectively reported immediately after cessation 63 and confirmed in other cases at 48 hours. 63 Recovery times, however, were as long as 4 months.…”
Section: Irreversibility/reversibility Of Sensorineural Hearing Lossmentioning
confidence: 83%
See 1 more Smart Citation
“…This antibiotic is considered relatively safe in adults, children, and pregnant women [13]. However, a number of side effects have been identified especially with intravenous administration, which may be associated with gastrointestinal disturbances, ototoxicity, and pain and inflammation of the injection site [14] The development of resistant bacteria, [15] and its association with proarrhythmic events [16] have also been reported. The latter risk has been attributed to QT prolongation (summation of action potential of ventricular myocytes), which can lead to a life-threatening arrhythmia; however, susceptible patients usually have other co-factors such as old age, heart disease, and exposure to other QT prolonging drugs [17].…”
Section: Azithromycinmentioning
confidence: 99%
“…ketoconazole) and appears to recover in the range of 4 to 11 weeks after discontinuing the macrolide. 14 In the most recent study of long-term macrolide therapy in chronic disease, Albert et al, 15 reported hearing decrements in 25% of subjects taking azithromycin and 20% of subjects allocated to placebo (p ¼ 0.04). Discontinuation of treatment led to improvements in audiogram results in 34% of patients taking azithromycin vs. 38% of patients taking placebo.…”
Section: Issues In Development Of Anti-inflammatory Macrolidesmentioning
confidence: 99%